2015
DOI: 10.1021/acs.macromol.5b00804
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Periodic Surface Structures on Conjugated Polymers: Poly(3-hexylthiophene)

Abstract: In this work, we report on the surface patterning of semiconducting Poly(3-hexylthiophene) (P3HT) thin films by means of Laser Induced Periodic Surface Structures (LIPSS). Two different laser wavelengths, 266 nm and 532 nm, and a broad range of fluences and number of pulses have been used in order to optimize the LIPSS morphology. Ripples period and depth can be tuned by laser parameters. In particular, the high optical absorption of P3HT at 532 nm enables the formation of well-ordered nanostructures with peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(84 citation statements)
references
References 59 publications
8
76
0
Order By: Relevance
“…Also naturally-derived polymers such as chitosan and its 50/50 wt. % blend with the synthetic polymer polyvinylpyrrolidone (PVP) [71,73] and the poly conjugated polymer poly(3hexylthiophene) (P3HT) have been reported to form LIPSS [49]. Ripple formation appears after laser irradiation at an appropriate wavelength, fluence range, well below the ablation threshold, and with a given number of pulses.…”
Section: Lipss Formation In Polymers Using Nanosecond Laser Pulsesmentioning
confidence: 99%
See 3 more Smart Citations
“…Also naturally-derived polymers such as chitosan and its 50/50 wt. % blend with the synthetic polymer polyvinylpyrrolidone (PVP) [71,73] and the poly conjugated polymer poly(3hexylthiophene) (P3HT) have been reported to form LIPSS [49]. Ripple formation appears after laser irradiation at an appropriate wavelength, fluence range, well below the ablation threshold, and with a given number of pulses.…”
Section: Lipss Formation In Polymers Using Nanosecond Laser Pulsesmentioning
confidence: 99%
“…In the case of polymers, several studies have shown that irradiation by a polarized laser beam induces self-organized ripple structure formation within a narrow fluence range, well below the ablation threshold [39,44,45,47,48]. As an example Figure 1 illustrates a typical ripple structure on poly(3-hexyl thiophene), P3HT, as observed by atomic force microscopy (AFM) [49]. reference [49].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Irradiation parameters (fluence and number of pulses) were chosen according to previously reported systematic experiments related to LIPSS formation on P3HT 44 .…”
Section: Laser Induced Periodic Surface Structures (Lipss)mentioning
confidence: 99%